Profiling of aminoxyTMT-labeled bovine milk oligosaccharides reveals substantial variation in oligosaccharide abundance between dairy cattle breeds - Robinson, Randall C. (Sci Rep, 2019)
Free milk oligosaccharides are bioactive molecules that function as prebiotics and prevent infections that commonly afflict developing infants. To date, few publications have examined the factors affecting bovine milk oligosaccharide production among cattle in the dairy industry. Here we have applied a high-throughput isobaric labeling technique to measure oligosaccharide abundances in milk collected from Danish Holstein-Friesian and Jersey dairy cattle by liquid chromatography-mass spectrometry. With a total of 634 milk samples, this collection represents the largest sample set used for milk oligosaccharide profiling in the current literature. This study is also the first to use isobaric labeling for the purpose of measuring free oligosaccharides in a real sample set. We have identified 13 oligosaccharides that vary significantly by breed, with most structures being more abundant in the milk of Jersey cattle. The abundances of several oligosaccharides were increased in second-parity cows, and correlations between the abundances of oligosaccharide pairs were identified, potentially indicating similarities in their synthetic pathways. Fucosylated oligosaccharide structures were widely identified among both breeds. Improving our understanding of oligosaccharide production will aid in developing strategies to recover these compounds from processing streams and may enable their use as a functional ingredient in foods for infants and adults.